Longitudinal cytokine and multi-modal health data of an extremely severe ME/CFS patient with HSD reveals insights into immunopathology, and disease severity - Jahanbani, Fereshteh; Sing, Justin Cyril; Maynard, Rajan Douglas; Jahanbani, Shaghayegh; Dafoe, Janet; Dafoe, Whitney; Jones, Nathan; Wallace, Kelvin J.; Rastan, Azuravesta; Maecker, Holden T.; Röst, Hannes L.; Snyder, Michael P.; et al. (Frontiers in Immunology, 2024)
Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) presents significant challenges in patient care due to its intricate multisystem nature, comorbidities, and global prevalence. To address these complexities, we employed a comprehensive approach, integrating longitudinal cytokine profiling with extensive clinical, health, textual, pharmaceutical, and nutraceutical data, and performed personalized analyses using AI. Focusing on an exceptionally severe ME/CFS patient with hypermobility spectrum disorder (HSD) and marginal symptom improvements, our study highlights the dynamic nature of symptoms, severity, triggers, and modifying factors. As part of this study, we introduced an updated platform and two applications, ME-CFSTrackerApp, and LexiTime, facilitating real-time symptom tracking and enhancing physician-patient communication. Our longitudinal cytokine profiling underscores the significance of Th2-type cytokines and synergistic activities between mast cells and eosinophils, leading to skewing of Th1 toward Th2 immune responses in ME/CFS pathogenesis, especially in cognitive impairment and sensorial intolerance. This suggests a potentially shared underlying mechanism with major comorbidities. Additionally, our data reveal potential roles of BCL6 and TP53 pathways in ME/CFS etiology and emphasize the importance of investigating low-dose drugs with partial agonist activity in ME/CFS treatment. Our analyses underscore the patient-centered care approach for better healthcare management.